Strategic Partnerships for Defense Industry Advancement in Developing Nations: Case Studies of Indonesia and Malaysia - Lubis, Lia Aulia; Banyu Perwita, Anak Agung; Eko Hadisancoko, Rizeriu (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study analyzes how defense diplomacy can contribute to enhancing the defense industry, particularly in developing countries like Indonesia and Malaysia. Through case studies of these two countries, the research explains the mechanisms of strategic collaboration that promote growth and innovation in the defense industry. In Indonesia, strategic partnerships with countries such as China, Hungary, Australia, and India have facilitated technology transfers and knowledge exchanges to boost self-reliance in defense production. In Malaysia, partnerships with countries like the United States, Australia, and Turkey, as well as multinational defense firms, have supported local technological development and integration into the global supply chain. Defense diplomacy plays a crucial role in strengthening defense capabilities and promoting economic growth and regional stability in developing countries